Application of Principle Component Analysis in the Mapping of Hydrothermal Alteration Using Landsat 8 Image in Kokap, Kulon Progo - Raharja, Bayu (Departemen Teknik Geologi, 2019)
The presence of gold mineralization in Kokap, Kulon Progo as a result from hydrothermal alteration has been proven by several researchers through geochemical analysis. Alteration mapping with optical remote sensing images in the tropical areas is very difficult, due to atmospheric conditions, dense vegetation cover, and rapid weathering. This study aims to assess the ability of Landsat 8 images in mapping of hydrothermal alteration in Kokap, Kulon Progo with the Principles Component Analysis (PCA) method. Multispectral classification with the maximum likelihood algorithm is then performed to map the alteration types based on PC images and observation data in the field. Two alteration zones were succeeded be mapped; argillic zone and propylitic zone. The success of hydrothermal alteration mapping is then evaluated statistically using confusion matrix. The acceptable level of accuracy is 85% with a kappa coefficient greater than 0.8. The results showed that the best PCA were given by a combination of band ratio images of 5:2 and 6:7 with an accuracy of 56.4% and kappa coefficient of 0.36 which is below acceptance standard. The combination of Landsat 8 with ALOS Palsar DEM succeeded in increasing accuracy to 59.5% with kappa coefficient of 0.4.